Investigation and Improvement of Option Valuation in Monte Carlo Method - Song, Ying (2019)
This paper attempts to study and explore the most commonly used option pricing models. As we will see in Chapter 2, the classic Black-Scholes model, the jump diffusion model, the binary tree model, and the Monte-Carlo valuation method are widely used for option pricing. A large amount of empirical evidence in the literature tests the validity of the model based on historical data. This paper uses the dual method to improve the Monte-Carlo estimation model and examine its simulation effect on historical data.